Urgensi Judicial Review dalam Tata Hukum Indonesia - Ni’matul Huda (Fakultas Hukum Universitas Islam Indonesia, 2008)
The attendence of institution which has an authority to conduct judicial review in the perspective of democratic state will establish a system to mantain the democratic mechanism to be done in the framework of democratic legal state.